Analysis of GPS data at Syowa Station and IGS tracking stations - Yamada, Akiko; Maruyama, Kazushi; Ootaki, Osamu; Itabashi, Akifusa; Hatanaka, Yuki; Miyazaki, Shin-ichi; Negishi, Hiroaki; Higashi, Toshihiro; Nogi, Yoshifumi; Kanao, Masaki; Doi, Koichiro (National Institute of Polar Research, 1998)
P(論文) The 36th Japanese Antarctica Research Expedition (JARE-36, 1995) built a Global Positioning System (GPS) station, SYOG, at Syowa Station in Antarctica. We analyzed GPS data of Syowa Station and the tracking stations of International GPS Service for Geodynamics (IGS) for the quality check of Syowa GPS data. GPS data were analyzed by Precise Point Positioning strategy implemented in GIPSY-OASIS n software developed by Jet Propulsion Laboratory. The site coordinates at the epoch of 1997.0 and velocities of these GPS stations were estimated by applying a velocity model to the obtained time series of site coordinates. The plate motion of the Antarctic plate and its internal deformation are discussed using these results. The Euler vector of the Antarctic plate was estimated from displacement velocities of SYOG and five IGS sites on the Antarctic plate. This result was derived only from GPS site velocities and supports the NNR NUVEL-1A model (C. DEMETS et al: Geophys. Res. Lett., 21, 2191, 1994). departmental bulletin paper